LANGUAGE POLITENESS IN THE CONVERSATION BETWEEN LECTURERS IN WHATSAPP CHATTING GROUP - Emeliya Sukma Dara Damanik (UIN Sumatera Utara, 2019)
This study investigates the occurrences of maxims in the conversation between lecturers in “ WhatsApp”. This study applied qualitative research by collecting the data from WhatsApp and the other source which supports to research. Based on the data, it can be found that the lecturers use six maxim proposed by Leech. They use tact, generosity, approbation, modesty, agreement and sympathy maxim. From the six maxims, the lecturers tend to use agreement maxim in conversation. They use Whatsapp as the media for communication in sharing information, discussing or solving the problem related to increasing of university. Finally, the writer concluded that the conversation between lecturers in WhatsApp group can be said “polite”.